Associations of serum creatinine and blood urea nitrogen with depressive symptoms among community-dwelling older adults in Guangzhou, China: a cross-sectional study - Huang, Jinping; Fu, Yuanzheng; Fu, Yushui; Pan, Yangjian; Hu, Yurong; Zhang, Jinquan; Guo, Wanwei; Du, Xiaoyan (Frontiers in Psychiatry, 2026)
BackgroundDepression is a common and serious mental health concern among older adults, with depressive symptoms highly prevalent in elderly populations across China. Although several studies have examined the associations between renal biomarkers—such as serum creatinine (Scr) and blood urea nitrogen (BUN)—and depressive symptoms, evidence remains limited, particularly in community-dwelling older adults. This study aimed to investigate the associations of renal biomarkers (Scr, BUN, and their ratio) with depressive symptoms in a community-based cohort of older adults in Guangzhou, China.MethodsThis cross-sectional study included 1, 994 adults aged ≥ 65 years from community-based health screenings in Guangzhou. Depressive symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9). Renal function was evaluated using Scr, BUN, and the BUN/Scr ratio. Multivariable logistic regression models were used to assess the association between these renal biomarkers and depressive symptoms, adjusting for potential confounders including age, sex, body mass index (BMI), and chronic disease history. To ensure robustness, we conducted sensitivity analyses by substituting Scr with estimated glomerular filtration rate (eGFR). Restricted cubic splines were used to evaluate dose-response shapes. Subgroup analyses tested for effect modification by sex, age group, BMI category, and histories of hypertension, diabetes, and dyslipidemia.ResultsAmong the 1, 994 participants (median age: 71 years), 158 (7.9%) exhibited depressive symptoms. After full adjustment, higher Scr (adjusted OR per 1 μmol/L = 1.002, 95% CI 1.000–1.004) and BUN (adjusted OR per 1 mmol/L = 1.064, 95% CI 1.007–1.123) were independently associated with higher odds of depressive symptoms, whereas the BUN/Scr ratio showed no significant association. In sensitivity analyses, eGFR was inversely associated with depressive symptoms (OR = 0.992, 95% CI 0.985–0.999). Restricted cubic spline analyses revealed an approximately linear dose–response for BUN (P for nonlinearity = 0.407). Subgroup analyses indicated significant effect modification for Scr, with stronger associations observed among participants aged ≥70 years, those with overweight/obesity (BMI ≥24 kg/m²), and those with hypertension (all P for interaction< 0.05).ConclusionsHigher Scr and BUN levels were independently associated with increased odds of depressive symptoms among community-dwelling older adults. The association of Scr with depression was particularly pronounced in older individuals, those with higher BMI, and those with hypertension.